Interplay between river discharge and tides in a delta distributary. (June 2015) - Leonardi, Nicoletta; Kolker, Alexander S.; Fagherazzi, Sergio
Highlights: We investigate the combined effect of river hydrograph and micro-tides. For unidirectional flow, tidal velocities increase with increasing discharge. Increasing discharge changes the phase lag between water level and velocity. High riverine flow increases seaward directed Eulerian residual currents. For very high discharge the effect of tides is surprisingly amplified. Abstract: The hydrodynamics of distributary channels has tremendous impact on nutrient and dissolved oxygen circulation, transport of sediments, and delta formation and evolution; yet many processes acting at the river–marine interface of a delta are poorly understood. This paper investigates the combined effect of river hydrograph and micro-tides on the hydrodynamics of a delta distributary. As the ratio between river flow to tidal flow increases, tidal flood duration at the distributary mouth decreases, up to the point when flow reversal is absent. Field measurements in a distributary of the Apalachicola Delta, Florida, USA, reveal that, once the flow becomes unidirectional, high-discharge events magnify tidal velocity amplitudes. On the contrary, while the flow is bidirectional, increasing fluvial discharge decreases tidal velocity amplitudes down to a minimum value, reached at the limit between bidirectional and unidirectional flow. Due to the different response of the system to tides, the transition from a bidirectional to a unidirectional flow triggers a change in phase lag between high water and high water slack. In the presence of high riverine flow, tidal dynamics also promote seaward directed Eulerian residual currents. During discharge peaks, these residual currents almost double mean velocity values. Our results show that, even in micro-tidal environments, tides strongly impact distributary hydrodynamics during both high and low fluvial discharge regimes.